The developmental effect of difenoconazole on zebrafish embryos: A mechanism research. (May 2016) - Mu, Xiyan; Chai, Tingting; Wang, Kai; Zhu, Lizhen; Huang, Ying; Shen, Gongming; Li, Yingren; Li, Xuefeng; Wang, Chengju
Abstract: Difenoconazole is a widely used triazole fungicide and has been reported to have negative impacts on zebrafish embryos. To investigate the mechanism of its developmental toxicity, zebrafish embryos were exposed to 0.5 and 2.0 mg/L difenoconazole for 96 h. The morphological and physiological indicators of embryo development were tested. The total cholesterol (TCHO) level, triglyceride (TG) level and malondialdehyde (MDA) content were measured at 96 hpf (hours post-fertilization). In addition, the transcription of genes related to embryo development, the antioxidant system, lipid synthesis and metabolism was quantified. Our results showed that a large suite of symptoms were induced by difenoconazole, including hatching regression, heart rate decrease, growth inhibition and teratogenic effects. 0.5 mg/L difenoconazole could significantly increase the TG content of zebrafish embryos at 96 hpf, while no apparent change in the TCHO and MDA level was observed post 96 h exposure. Q-PCR (quantitative real-time polymerase chain reaction) results showed that the transcription of genes related to embryonic development was decreased after exposure. Genes related to hatching, retinoic acid metabolism and lipid homeostasis were up-regulated by difenoconazole. Graphical abstract: Highlights: Difenoconazle could induce cardiac effect and spine deformation in zebrafish embryos. Difenoconazole could inhibit expression of genes involved in embryo growth. Genes related in retinoic acid metabolism and lipid homeostasis were up-regulated by difenoconazole. No apparent change of TCHO and MDA was observed after exposure. Abstract : Genes related to embryonic development were decreased after difenoconazole exposure. Genes related to hatching, retinoic acid metabolism and lipid homeostasis were up-regulated by difenoconazole.